2007
DOI: 10.1016/j.susc.2007.09.028
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of Ni ultrathin films on Mo(110) and W(100) studied by LEED and STM

Abstract: The morphology of ultrathin Ni films on Mo(110) and W(100) has been studied by low-energy electron diffraction and scanning tunneling microscopy. Ni films grow pseudomorphically on Mo(110) at 300 K for a coverage of 0.15 ML. A (8 × 1) structure is found at 0.4 ML, which develops into a (7×1) structure by 0.8 ML as the film undergoes a structural change to fcc Ni(111) at 6 ML. The growth mode switches from layer-by-layer to Stranski-Krastanov between 4 ML and 6 ML. Annealing at around 850 K results in alloying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The slight shift in the Ni 2p 3/2 peak position to a higher binding energy value at 300 K compared to that from the bulk Ni can be contributed to the initial and final state effects resulting from the low coordination of the Ni atoms in very small clusters. , As shown in the STM image (Figure b), at room temperature, very small Ni particles that are less than 2.0 nm wide and 0.5 nm high are formed on the ceria surface. These particles are two-dimensional considering the height for an atomic layer of Ni in STM is between 2 and 3 Å . On the basis of the thermodynamics, the formation of two-dimensional islands on an oxide surface should occur if the interfacial energy between the metal and the oxide (γ m/o ) is smaller than the difference between the surface free energy for the metal (γ v,m ) and the oxide (γ v,o ) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The slight shift in the Ni 2p 3/2 peak position to a higher binding energy value at 300 K compared to that from the bulk Ni can be contributed to the initial and final state effects resulting from the low coordination of the Ni atoms in very small clusters. , As shown in the STM image (Figure b), at room temperature, very small Ni particles that are less than 2.0 nm wide and 0.5 nm high are formed on the ceria surface. These particles are two-dimensional considering the height for an atomic layer of Ni in STM is between 2 and 3 Å . On the basis of the thermodynamics, the formation of two-dimensional islands on an oxide surface should occur if the interfacial energy between the metal and the oxide (γ m/o ) is smaller than the difference between the surface free energy for the metal (γ v,m ) and the oxide (γ v,o ) .…”
Section: Resultsmentioning
confidence: 99%
“…These particles are two-dimensional considering the height for an atomic layer of Ni in STM is between 2 and 3 Å. 35 On the basis of the thermodynamics, the formation of twodimensional islands on an oxide surface should occur if the interfacial energy between the metal and the oxide (γ m/o ) is smaller than the difference between the surface free energy for the metal (γ v,m ) and the oxide (γ v,o ). 36 Although the surface free energy of Ni (∼1.7 J/m 2 ) is larger than that of ceria (0.7 J/m 2 ), Ni tends to wet the ceria surface which indicates a strong interaction between the two.…”
Section: Resultsmentioning
confidence: 99%
“…Characterization of the Ni/Mo(110) and Co/Mo(110) surfaces has been extensively studied via LEED, STM, and AES; the investigations of the growth of Ni and Co overlayers on Mo(110) show that both Ni and Co grow layer by layer on Mo(110) at room temperature and form 3D islands upon annealing to >600 K. Reactions of alcohols on clean Mo(110) and modified Mo(110) have been largely reported by Friend’s group via surface science studies. However, the investigation of reactions of aldehydes on Mo(110) is limited; Mei et al studied the reaction pathways of acetaldehyde via periodic spin-polarized density functional theory (DFT) simulations, and Queeney et al reported the reaction of formaldehyde on Mo(110) using temperature-programmed reactions and infrared reflectance absorbance spectroscopy . To the best of our knowledge, there has been no experimental UHV study of C3 aldehyde on pure Mo(110) and/or metal-modified Mo(110) surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Until now, the surface structures and growth modes of various adsorbate metals (e.g. Cu [3], Co [4], Fe [5], Ni [6], Mg [7], Ba [8], K [9], S [10], In [11], Ag [12][13][14][15][16][17], Au [18][19], Sn [20][21], Pb [22][23][24][25], etc.) on the Mo (110) substrates have been investigated by a variety of experimental and theoretical methods in a number of works.…”
Section: Introductionmentioning
confidence: 99%
“…Until now, the surface structures and growth modes of various adsorbate metals (e.g. Cu [3], Co [4], Fe [5], Ni [6], Mg [7], Ba [8], K [9], S [10], In [11], Ag [12][13][14][15][16][17], Au [18,19], Sn [20,21], Pb [22][23][24][25], etc) on Mo (110) substrates have been investigated by a variety of experimental and theoretical methods in a number of works. Recently, the formation of oxide layers on transition metal (TM) surfaces has also received considerable attention [26][27][28][29], including the Mo (110) surface [30,31].…”
Section: Introductionmentioning
confidence: 99%